Tinjauan Yuridis terhadap Peraturan Menteri Perdagangan tentang Penetapan Harga Eceran Tertinggi (HET) Minyak Goreng Sawit Tahun 2022: (Studi Kasus Putusan Pengadilan Niaga Nomor 1,2,3,4,5,6,7/Pdt.Sus-KPPU/2023/PN Niaga Jkt Pst) - Gunawan Widjaja; Songga Aurora Abadi; Robert Iskandar (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study analyzes the Highest Retail Price (HET) policy for palm cooking oil. of palm cooking oil implemented by the Indonesian government through MOT Regulation of the Minister of Trade (Permendag) Number 1 of 2022 as revoked based on Permendag Number 6 of 2022 concerning the Determination of HET of Palm Cooking Oil, and its implications for business competition based on Law No. 5 of 1999 on the Prohibition of Monopolistic Practices. based on Law No.5/1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. and Unfair Business Competition. The price ceiling policy aims to protect consumers from uncontrolled price increases, especially for low-income households. low-income communities. However, its implementation has caused negative impacts such as scarcity and losses for producers, which was found to have violated Article 19 letter c of Law No.5 Year 1999 by KPPU. violated Article 19 letter c of Law No. 5 Year 1999 by KPPU. Producers filed an objection, and the Central Jakarta Commercial Court ruled that the scarcity of cooking oil was the impact of the single price ceiling policy, and therefore the KPPU's decision was canceled. This research uses normative legal methods by analyzing legal principles in court decisions and related regulations. The results show that the price ceiling policy needs to be re-evaluated to balance the interests of consumers and producers. balance the interests of consumers and producers. Implications of the court decision court decision is the need for stricter supervision and participation of stakeholders in the formulation of future price ceiling policies. stakeholders in the formulation of the price ceiling policy in the future. This research contributes theoretically in the field of competition law and practically as a reference for policy makers. as a reference for policy makers.